Epitaxial structure of LED quantum well and growth method thereof
By using the superlattice structure formed by alternatingly grown indium gallium nitrogen layer and treatment layer in the Micro-LED quantum well, the problem of difficulty in improving external quantum efficiency under small current density is solved, and the LED light efficiency is significantly improved.
Patent Information
- Application Number
- CN202510000250.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-02-07
AI Technical Summary
In the existing Micro-LED display technology, as the size decreases, the external quantum efficiency sags severely, and the peak efficiency moves toward the direction of high current density, resulting in difficulty in improving external quantum efficiency under small current density.
By using the superlattice structure formed by alternately growing indium gallium nitrogen layer and treatment layer in the epitaxial structure of the LED quantum well, the thickness of the InGaN layer is controlled to reduce compressive stress, and maintain ammonia and three during the growth process Constant time treatment of methyl indium.
It significantly improves the light efficiency of LEDs under small current density, reduces the defects and surface roughness of the InGaN layer, and improves the crystal quality of the quantum well.
Smart Images

Figure CN119403313A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor devices, and in particular to an epitaxial structure of an LED quantum well and a growth method thereof. Background Art
[0002] Micro-LED display technology has many advantages such as high brightness, short response time, high resolution, high color contrast, wide color gamut, low power consumption and long service life. It is an ideal light source and image display source in display, and is also regarded by many optical component manufacturers as a breakthrough core device in display.
[0003] As we all know, as the size of Micro-LEDs shrinks, the external quantum efficiency droops severely, and the peak efficiency moves toward high current density. The existing technology proposes that the current for Micro-LED display applications is very small, requiring control at the microampere or even nanoampere level, and the corresponding current density is required to be 0.02~2A / cm 2 Even smaller, so improving the external quantum efficiency under low current density is the key to improving the efficiency of Micro-LED.
[0004] Since the Shockley Read Hall (SRH) model non-radiative recombination rate is proportional to the carrier concentration, and the radiative recombination rate is proportional to the square of the carrier concentration, and the carrier concentration is low at low current density, the internal quantum efficiency of LEDs at low current density is mainly determined by the SRH non-radiative recombination related to defects. Therefore, in order to improve the light efficiency of Micro-LEDs, it is key to improve the crystal quality of quantum wells and reduce the non-radiative recombination caused by defects in quantum wells.
[0005] When epitaxially growing indium gallium nitride (InGaN) quantum wells by metal organic chemical vapor deposition (MOCVD), it is necessary to perform the growth at a relatively low temperature. The low growth temperature and large strain lead to more defects in the quantum wells, such as nitrogen vacancies, stacking faults, and rough interfaces caused by insufficient atomic surface migration. These defects serve as the center of non-radiative recombination, reducing the probability of radiative recombination. In addition, due to the poor solid solubility of indium nitride (InN) in gallium nitride (GaN) materials, the control window for growing high indium (In) component InGaN materials is small, and it is easy to produce component segregation, resulting in residual In metal on the surface of InGaN, which leads to poor interface characteristics and other adverse effects, resulting in a large number of black spots in the fluorescence morphology, further reducing the crystal quality of the quantum well. Summary of the invention
[0006] The present invention aims to at least improve one of the technical problems existing in the prior art. To this end, the present invention proposes an epitaxial structure of an LED quantum well and a growth method thereof.
[0007] The technical solution of the present invention is as follows: An epitaxial structure of an LED quantum well, comprising: An active layer, wherein the active layer is composed of a plurality of unit structures stacked periodically, each unit structure comprising a quantum well layer, a cap layer and a quantum barrier layer grown in sequence, wherein: The quantum well layer includes a superlattice structure formed by alternately grown indium gallium nitride layers and treatment layers, wherein the thickness N of the indium gallium nitride layer is 2.5 angstroms to 10 angstroms; and ammonia and indium need to be introduced during the growth of the treatment layer.
[0008] In a possible technical solution, further, the number of alternations L between the indium gallium nitride layer and the treatment layer is 3 to 20 times, so that the thickness of InGaN in the quantum well layer is very thin, less than three atomic layers, which can greatly reduce the compressive stress on InGaN and improve the crystal quality of the quantum well.
[0009] In a possible technical solution, further, the unit structure has a periodic stacking number of 1 to 9 times.
[0010] In a possible technical solution, further, the material of the cap layer is any one of a gallium nitride layer, an indium gallium nitride layer, and an aluminum gallium nitride layer, or a combination thereof; The material of the quantum barrier layer is any one of a gallium nitride layer, an indium gallium nitride layer, and an aluminum gallium nitride layer or a combination thereof, so that the LED quantum well has excellent performance and broad application prospects.
[0011] An epitaxial growth method for LED quantum wells, which realizes the growth process in a reaction chamber and is used to prepare the above-mentioned unit structure, comprises: Step 100, growing a quantum well layer, includes the following process: Step 101, InGaN layer growth process: controlling the temperature of the reaction chamber to be maintained at a first temperature Temp1, introducing ammonia, nitrogen, triethylgallium and trimethylindium for a first growth time T1, and completing the InGaN layer growth process; Step 102, a process of growing a treatment layer: controlling the temperature of the reaction chamber to be maintained at a second temperature Temp2, introducing ammonia gas and trimethyl indium to maintain a constant temperature for a second time T2, and completing the process of growing the treatment layer; Repeat the above growth process of the InGaN layer and the treatment layer to obtain a quantum well layer that meets the thickness requirement; Step 200, growing a cap layer, controlling the temperature of the reaction chamber to be maintained at a third temperature Temp3, introducing ammonia, triethylgallium and trimethylaluminum for a third growth time T3, and obtaining a cap layer; Step 300, growing a quantum barrier layer, controlling the temperature of the reaction chamber to be maintained at a fourth temperature Temp4, introducing ammonia, triethylgallium and trimethylaluminum to grow for a fourth time T4, and obtaining the unit periodic structure.
[0012] In a possible technical solution, further, during the growth of the treatment layer, the flow ratio of the ammonia gas and the trimethyl indium is in the range of 100 to 2000. On the one hand, the growth rate can be accurately controlled to meet specific process requirements, help reduce defects and impurities, and improve the purity and integrity of the crystal. On the other hand, a smoother and more uniform InGaN layer surface can be obtained, which helps to ensure the stability and repeatability of the process, reduce differences between production batches, and improve product quality and consistency.
[0013] In a possible technical solution, further, the first temperature Temp 1、 The second temperature Temp2 and the third temperature Temp3 are the same, which simplifies the process while reducing the InGaN compressive stress and ensures a good match between the temperatures.
[0014] In a possible technical solution, further, the fourth temperature Temp4 is higher than the second temperature Temp2.
[0015] In a possible technical solution, further, the second time T2 is in the range of 3 seconds to 30 seconds, which can effectively control the growth time of the treatment layer and improve the luminous efficiency of the LED.
[0016] An LED chip, wherein the LED chip comprises the epitaxial structure of the LED quantum well as described above.
[0017] The epitaxial structure of an LED quantum well and the growth method thereof of the present invention have at least one of the following beneficial effects: 1. By thinning the InGaN layer during the quantum well growth process to make its single layer thickness 5% to 15% of the InGaN thickness in a conventional quantum well, the compressive stress on InGaN can be greatly reduced and the crystal quality of the quantum well can be improved.
[0018] 2. The present invention maintains a constant time treatment of ammonia and trimethylindium (TMIn) after a short period of InGaN growth, which can reduce nitrogen vacancy defects in InGaN, and at the same time reduce the surface roughness of InGaN and the segregation of In in InGaN, thereby greatly improving the crystal quality of the quantum well.
[0019] 3. The present invention can significantly improve the light efficiency of LEDs at low current density.
[0020] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 Schematic diagram of a conventional quantum well epitaxial structure.
[0023] Figure 2 It is a schematic diagram of the structure of the active layer and its LED quantum well of the present invention.
[0024] Figure 3 This is a comparison diagram of the photoelectric parameters of the LED chip of the present invention and the conventional quantum well LED chip; Figure 4 This is a comparison chart of the photoelectric parameters of sample A and sample B after the growth time of the treatment layer of the LED of the present invention is changed.
[0025] Reference numerals: 100 - substrate; 200 - buffer layer; 300 - non-doped GaN layer; 400 - n-type GaN layer; 500 - stress release layer; 600 - active layer; 610 - quantum well layer; 611 - cap layer; 612 - quantum barrier layer; 620 - InGaN layer; 621 - treatment layer; 700 - electron blocking layer; 800 - p-type GaN layer. DETAILED DESCRIPTION
[0026] The embodiments of the present invention are described in detail below. The embodiments described with reference to the accompanying drawings are exemplary. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0027] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be an intermediate element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be an intermediate element at the same time.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0029] The terms "first", "second", "third", etc. in the specification and claims of the present application and the drawings are used to distinguish different objects rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a series of steps or units are included, or optionally, steps or units not listed are included, or optionally, other steps or units inherent to these processes, methods, products or devices are included.
[0030] Comparative Example like Figure 1 As shown, the conventional quantum well epitaxial structure prepared in the present application includes a silicon substrate 100, an aluminum nitride (AlN) buffer layer 200, an undoped GaN layer 300, an n-type GaN layer 400, a stress release layer 500, an active layer 600, an electron blocking layer 700 and a p-type GaN layer 800. The preparation method thereof specifically includes the following steps: Step 1: Place a silicon (Si) substrate 100 in a MOCVD reaction chamber, raise the temperature inside the reaction chamber to 1210° C., introduce hydrogen, and maintain the hydrogen atmosphere for 10 minutes to clean the surface of the silicon substrate; Step 2: maintaining the temperature inside the reaction chamber at 1210° C. and the pressure at 20 Torr, introducing ammonia, hydrogen and trimethylaluminum into the reaction chamber, and growing an AlN buffer layer 200 on the surface of the cleaned silicon substrate, wherein the growth thickness of the AlN buffer layer 200 is 2800 angstroms; Step 3: lowering the temperature in the reaction chamber to 1170 degrees, increasing the pressure to 50 Torr, introducing ammonia, hydrogen and trimethyl gallium to grow a non-doped GaN layer 300, wherein the growth thickness of the non-doped GaN layer 300 is 5000 angstroms; Step 4: The temperature in the reaction chamber is lowered to 1130°C, and ammonia, hydrogen, trimethylgallium and silane are introduced to grow an n-type GaN layer 400, wherein the growth thickness of the n-type GaN layer 400 is 2 microns and the doping concentration is 3×10 18 / cm 3 ; Step 5: lowering the temperature in the reaction chamber to 920° C., introducing ammonia, nitrogen, triethylgallium and trimethylindium to grow a stress release layer 500, wherein the growth thickness of the stress release layer 500 is 2500 angstroms; Step 6: growing the active layer 600, including growing the quantum well layer 610, the cap layer 611 and the quantum barrier layer 612 respectively, wherein: During the growth of the quantum well layer 610, the growth temperature in the reaction chamber is controlled to be maintained at 760°C, the growth time is 226s, and ammonia, triethylgallium and trimethylindium are introduced during the growth process; During the growth of the cap layer 611, the growth temperature in the reaction chamber is controlled to be 760°C, the growth time is 50 seconds, and ammonia, triethylgallium and trimethylaluminum are introduced during the growth process; During the growth of the quantum barrier layer 612, the growth temperature in the reaction chamber is controlled to be 950°C, the growth time is 600s, and ammonia, triethylgallium and trimethylaluminum are introduced during the growth process; Step 7: Raise the temperature in the reaction chamber to 980 degrees, introduce ammonia, nitrogen, triethylgallium and trimethylaluminum to grow an electron blocking layer 700, wherein the solid phase aluminum component accounts for 20%, and the thickness of the electron blocking layer 700 is 120 angstroms; Step 8: Keeping the temperature in the reaction chamber constant, introduce ammonia, triethylgallium and dicyclopentadienyl magnesium to grow a p-type GaN layer 800, wherein the thickness of the p-type GaN layer 800 is 600 angstroms and the doping concentration is 2×10 20 / cm 3 .
[0031] The epitaxial wafer of the comparative example was processed into a chip of 1000 micron × 1000 micron through a chip manufacturing process, and its photoelectric performance was tested after being packaged in the form of LUXEON. Figure 3 As shown in the dashed lines in (a) and (b), Figure 3 This is a comparison chart of the photoelectric parameters of the LED chip of Example 1 of the present invention and the LED chip of the comparative example: Figure 3 (a) is a comparison diagram of the external quantum efficiency of the comparative LED and the LED of the present invention as a function of current density, wherein the dotted line is the comparative LED and the solid line is the LED of the present invention; Figure 3 (b) is a graph showing the variation of the peak wavelength of the comparative LED and the LED of the present invention with the current density, wherein the dotted line is the comparative LED and the solid line is the LED of the present invention.
[0032] Example 1 like Figure 1 and Figure 2 As shown, this embodiment provides an epitaxial structure of an LED quantum well, which includes a silicon substrate 100, an AlN buffer layer 200, an undoped GaN layer 300, an n-type GaN layer 400, a stress release layer 500, an active layer 600, an electron blocking layer 700 and a p-type GaN layer 800, wherein the active layer 600 is composed of a plurality of unit periodic structures, each unit periodic structure includes a quantum well layer 610, a cap layer 611 and a quantum barrier layer 612 grown sequentially from bottom to top, wherein: The quantum well layer 610 is a superlattice periodic structure formed by alternately grown InGaN layers 620 and treatment layers 621 , wherein the thickness N of the InGaN layers 620 is 2.5 angstroms to 10 angstroms; and a treatment layer 621 is reserved between every two adjacent InGaN layers 620 .
[0033] It should be noted that the period number L of the superlattice periodic structure is 3 to 20, which makes the thickness of InGaN in the quantum well layer very thin, less than three atomic layers, which can greatly reduce the compressive stress on InGaN and improve the crystal quality of the quantum well.
[0034] It should be noted that the number of periods of the unit periodic structure is 1 to 9.
[0035] The epitaxial growth method of the LED quantum well of this embodiment implements the growth process in a reaction chamber, which includes: Step 1: Place a silicon (Si) substrate 100 in a MOCVD reaction chamber, raise the temperature inside the reaction chamber to 1210° C., introduce hydrogen, and maintain the hydrogen atmosphere for 10 minutes to clean the surface of the silicon substrate.
[0036] Step 2: Maintaining the temperature inside the reaction chamber at 1210°C and the pressure at 20 Torr, introducing ammonia, hydrogen and trimethylaluminum into the reaction chamber, and growing an AlN buffer layer 200 on the surface of the cleaned silicon substrate, wherein the growth thickness of the AlN buffer layer 200 is 2800 angstroms.
[0037] Step 3: The temperature in the reaction chamber is lowered to 1170 degrees, the pressure is increased to 50 Torr, and ammonia, hydrogen and trimethylgallium are introduced to grow a non-doped GaN layer 300, wherein the growth thickness of the non-doped GaN layer 300 is 5000 angstroms.
[0038] Step 4: The temperature in the reaction chamber is lowered to 1130°C, and ammonia, hydrogen, trimethylgallium and silane are introduced to grow an n-type GaN layer 400, wherein the growth thickness of the n-type GaN layer 400 is 2 microns and the doping concentration is 3×10 18 / cm 3 .
[0039] Step 5: Lower the temperature in the reaction chamber to 920° C., introduce ammonia, nitrogen, triethylgallium and trimethylindium to grow a stress release layer 500, wherein the growth thickness of the stress release layer 500 is 2500 angstroms.
[0040] Step 6: growing the active layer 600, including growing the quantum well layer 610, the cap layer 611 and the quantum barrier layer 612 respectively, including the following steps: Step 100, growing a quantum well layer 610, includes the following process: Step 101, InGaN layer 620 growth process: control the temperature of the reaction chamber to maintain at 760° C., introduce ammonia, nitrogen, triethylgallium and trimethylindium for 20 seconds, and complete the InGaN layer growth process; Step 102, growth process of the treatment layer 621: control the temperature of the reaction chamber to be maintained at 760° C., introduce ammonia and trimethyl indium and keep them constant for 10 seconds to complete the growth process of the treatment layer; Repeating the above growth process of the InGaN layer and the treatment layer for 11 times to obtain a quantum well layer 610 that meets the thickness requirement; Step 200, growing a cap layer 611, controlling the temperature of the reaction chamber to be maintained at 760°C, introducing ammonia, triethylgallium and trimethylaluminum to grow for 50 seconds to obtain a cap layer; Step 300, growing a quantum barrier layer 612, controlling the temperature of the reaction chamber to be maintained at 950°C, introducing ammonia, triethylgallium and trimethylaluminum for 600 seconds, and obtaining a unit periodic structure; The active layer 600 is obtained by sequentially growing a plurality of unit periodic structures.
[0041] Step 7: Raise the temperature in the reaction chamber to 980 degrees, introduce ammonia, nitrogen, triethylgallium and trimethylaluminum to grow an electron blocking layer 700, wherein the solid phase aluminum component accounts for 20%, and the thickness of the electron blocking layer 700 is 120 angstroms.
[0042] Step 8: Keeping the temperature in the reaction chamber constant, introduce ammonia, triethylgallium and dicyclopentadienyl magnesium to grow a p-type GaN layer 800, wherein the thickness of the p-type GaN layer 800 is 600 angstroms and the doping concentration is 2×10 20 / cm 3 .
[0043] It should be noted that during the growth of the treatment layer 621, the flow ratio of the ammonia gas and the trimethyl indium is in the range of 100 to 2000. On the one hand, the growth rate can be accurately controlled to meet specific process requirements, help reduce defects and impurities, and improve the purity and integrity of the crystal. On the other hand, a smoother and more uniform InGaN layer 620 surface can be obtained, which helps to ensure the stability and repeatability of the process, reduce differences between production batches, and improve product quality and consistency.
[0044] It should be noted that the material of the cap layer is any one of a gallium nitride layer, an indium gallium nitride layer, and an aluminum gallium nitride layer, or a combination thereof.
[0045] It should be noted that the material of the quantum barrier layer is any one of a gallium nitride layer, an indium gallium nitride layer, and an aluminum gallium nitride layer, or a combination thereof.
[0046] The epitaxial structure of an LED quantum well and the growth method thereof of the present invention have at least one of the following beneficial effects: By thinning the InGaN layer during the quantum well growth process to make its single layer thickness 5% to 15% of the InGaN thickness in a conventional quantum well, the compressive stress on InGaN can be greatly reduced and the crystal quality of the quantum well can be improved.
[0047] The present invention maintains ammonia and trimethylindium (TMIn) treatment for a constant time after a short period of InGaN growth, which can reduce nitrogen vacancy defects in InGaN, and can also reduce the surface roughness of InGaN and the segregation of In in InGaN, thereby greatly improving the crystal quality of the quantum well.
[0048] The present invention can significantly improve the light efficiency of LEDs at low current density.
[0049] The epitaxial wafer of this embodiment is processed into a chip of 1000 microns × 1000 microns through a chip manufacturing process, and its photoelectric performance is tested after being packaged in the form of LUXEON. Figure 3 (a) and Figure 3 Compared with the conventional structure LED in the comparative example, the LED of the present invention has a current density of 0.07A / cm 2 When the external quantum efficiency is increased by 18%, the luminous efficiency of LED at low current density can be significantly improved; at a current density of 0.75A / cm 2 When the external quantum efficiency is increased by 4%.
[0050] Example 2 Taking Example 1 as a reference group, this example provides a test group based on Example 1 for parameter performance optimization.
[0051] The reference group was prepared in the same manner as in Example 1. The epitaxial wafer obtained was subjected to a chip manufacturing process to be made into a 1000 μm × 1000 μm chip as sample A. The photoelectric performance was tested after packaging in the form of LUXEON. Figure 4 As shown in (a), Figure 4 This is a comparison chart of the photoelectric parameters of sample A and sample B after the constant time treatment conditions of the LED of the present invention are changed: Figure 4 (a) is a graph showing the change of external quantum efficiency with current density, where the solid line is sample A and the dotted line is sample B; Figure 4 (b) is a graph showing the change of peak wavelength with current density, where the solid line is sample A and the dotted line is sample B; The preparation method of the test group was adjusted as follows based on Example 1: During the growth of the treatment layer 621, the ammonia and trimethyl indium were introduced into the reference group for 5 seconds instead of 10 seconds, and the remaining steps remained unchanged. The epitaxial wafer obtained was processed through the chip manufacturing process to be made into a 1000 micron × 1000 micron chip as sample B, and its photoelectric performance was tested after being packaged in the form of LUXEON. Figure 4 As shown in (b) in .
[0052] according to Figure 4 (a) and Figure 4 As shown in (b), at a current density of 0.35 A / cm 2 When , the peak wavelengths of sample A and sample B are the same, and the external quantum efficiency of sample A is 10% higher than that of sample B. The above embodiments illustrate that changing the constant time during the growth of the treatment layer 621 has a significant effect on the luminous efficiency of the LED, and the luminous efficiency of the LED can be further improved through the optimization experiment of the two-layer parameters.
[0053] It should be noted that the technical improvements made by optimizing the parameters of these two layers also belong to the present invention and are within the scope of protection of this application.
[0054] Example 3 This embodiment provides an LED chip, wherein the LED chip includes the epitaxial structure of the LED quantum well as described above.
[0055] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.
[0056] Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Mentioning "embodiment" in this article means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present embodiment application. The appearance of this phrase in various positions in the specification is not necessarily the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It can be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0057] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. An epitaxial structure of an LED quantum well, characterized in that: include: An active layer, wherein the active layer is composed of a plurality of unit structures stacked periodically, each unit structure comprising a quantum well layer, a cap layer and a quantum barrier layer grown in sequence, wherein: The quantum well layer includes a superlattice structure formed by alternately grown indium gallium nitride layers and treatment layers, wherein the thickness N of the indium gallium nitride layer is 2.5 angstroms to 10 angstroms; and ammonia and indium need to be introduced during the growth of the treatment layer.
2. The epitaxial structure of the LED quantum well according to claim 1, characterized in that: The number of alternations L between the InGaN layer and the treatment layer is 3 to 20 times.
3. The epitaxial structure of the LED quantum well according to claim 1, characterized in that: The unit structure has a stacking period of 1 to 9 times.
4. The epitaxial structure of the LED quantum well according to claim 1, characterized in that: The material of the cap layer is any one of a gallium nitride layer, an indium gallium nitride layer, and an aluminum gallium nitride layer, or a combination thereof; The material of the quantum barrier layer is any one of a gallium nitride layer, an indium gallium nitride layer, and an aluminum gallium nitride layer, or a combination thereof.
5. A method for epitaxial growth of LED quantum wells, wherein the growth process is carried out in a reaction chamber, characterized in that: For preparing the unit structure as claimed in claim 1, comprising: Step 100, growing a quantum well layer, includes the following process: Step 101, InGaN layer growth process: controlling the temperature of the reaction chamber to be maintained at a first temperature Temp1, introducing ammonia, nitrogen, triethylgallium and trimethylindium for a first growth time T1, and completing the InGaN layer growth process; Step 102, a process of growing a treatment layer: controlling the temperature of the reaction chamber to be maintained at a second temperature Temp2, introducing ammonia gas and trimethyl indium to maintain a constant temperature for a second time T2, and completing the process of growing the treatment layer; Repeat the above growth process of the InGaN layer and the treatment layer to obtain the quantum well layer that meets the thickness requirement; Step 200, growing a cap layer, controlling the temperature of the reaction chamber to be maintained at a third temperature Temp3, introducing ammonia, triethylgallium and trimethylaluminum for a third growth time T3, and growing the cap layer on the quantum well layer; Step 300, growing a quantum barrier layer, controlling the temperature of the reaction chamber to be maintained at a fourth temperature Temp4, introducing ammonia, triethylgallium and trimethylaluminum for a fourth growth time T4, growing the quantum barrier layer on the cap layer, and obtaining the unit structure.
6. The epitaxial growth method of LED quantum well according to claim 5, characterized in that: During the growth of the treatment layer, the flow ratio of the ammonia gas to the trimethyl indium is in the range of 100 to 2000.
7. The epitaxial growth method of LED quantum well according to claim 5, characterized in that: The first temperature Temp 1、 The second temperature Temp2 and the third temperature Temp3 are the same.
8. The epitaxial growth method of LED quantum well according to claim 5, characterized in that: The fourth temperature Temp4 is higher than the second temperature Temp2.
9. The epitaxial growth method of LED quantum well according to claim 5, characterized in that: The second time T2 ranges from 3 seconds to 30 seconds.
10. An LED chip, characterized in that: The LED chip includes the epitaxial structure of the LED quantum well according to any one of claims 1 to 4.
Citation Information
Patent Citations
Epitaxial structure and growing method for improving gallium nitride (GaN) based light-emitting diode (LED) lighting efficiency
CN103066174A
Light emitting diode and growth method thereof
CN104362237A
Novel LED quantum well and preparation method thereof
CN109300853A
Light-emitting diode epitaxial wafer and fabrication method thereof
CN109346575A
Light emitting diode epitaxial wafer and manufacturing method thereof
CN110993753A
Cited By
Method for measuring absorption coefficient of quantum well material
CN116465844A
A method for measuring the absorption coefficient of quantum well material
CN116465844B